Lima Barreto: ficção e biografia no contexto da Belle Époque - Bastos, Everton Luis (2020)
This research aims to analyze the construction of the character Lima Barreto in the contemporary novel O Passeador (2011), by Luciana Hidalgo. It seeks to verify, in particular, the character / author’s relations with the city and with the modernization processes of the then federal capital at the beginning of the Belle Époque and its combativeness with the republican regime at the time. In addition, a comparison with the biographical constructions about the same author will be established through his two biographies: A vida de Lima Barreto (1952), by Francisco de Assis Barbosa, and Lima Barreto: Triste visionário (2017), by Lilia Moritz Schwarcz, revealing that both fictional characters and biographical subjects are constructs that carry the positions and interests of their creators. The work is supported by the ideas of Marshall Berman, whose speech is shaped by an observation of 19th century modernity. From this perspective, investments are made in research on the first Republic of Brazil, in addition to the process of re-urbanization in the city of Rio de Janeiro. As a theoretical framework, the concepts of David Harvey and Hans Ulrich Gumbretcht were used, which will dialogue with the ideas of Roberto Schwarz and Jessé Souza with regard to the construction of Brazilian social identity. Finally, the works O Pacto autobiográfico (2008), by Philippe Lejeune and A ordem do discurso (1996), by Michel Foucault, as well as the important Literatura de urgência: Lima Barreto no domínio da loucura (2008), by Hidalgo , whose readings give support to understand and identify the different constructions of discourse in the spheres of fiction and biography and how much they have in common as an aesthetic product.